Development of Ca(oh)2-Based Geopolymer for Additive Manufacturing Using Construction Wastes and Nanomaterials - Mortada, Youssef; Kogbara, Reginald; Masad, Eyad; Kogbara, Reginald B.; Mansoor, Bilal; Seers, Thomas; Hammoud, Ahmad; Karaki, Ayman (Elsevier, 2023)
Recent growth in additive manufacturing (AM) or 3D printing in the construction field has motivated the development of various materials that vary in its composition and properties. This paper introduces, characterizes, and evaluates the performance of a sustainable and environmentally friendly geopolymer mixture composed of construction wastes. The geopolymer mixture has calcium hydroxide (Ca(OH)2) as the main alkaline activator and incorporates nanomaterials such as nano-silica and nano-clay to enhance its suitability for AM. The combined use of Ca(OH)2 for alkali activation, and nanomaterials for tailoring the behavior of construction wastes for 3D printing, is novel and addresses the shortcomings of conventional alkaline activators. The paper includes the outcomes of the analysis of the mechanical properties, printability, and microstructure of the geopolymer mixture. The 28-day compressive strength of the mixture reached 42 MPa with ambient temperature curing, which is comparable to traditional geopolymers. The inclusion of 1 wt % of nano-silica accelerated the geopolymerization process and led to the largest (35 %) reduction in the setting time. Similarly, incorporating 1 wt % of nano-clay led to reduction of the thermal conductivity from 0.709 W/mK to 0.505 W/mK, due to the introduction of thermal barriers. The printability of the studied waste-based geopolymer mixture was validated through the successful fabrication of a 3D-printed model. © 2023 The Authors
Keywords: Additive manufacturing; Geopolymer; Nanomaterials; Sustainability; Waste